Does longer duration of breastfeeding prevent childhood asthma in low-income families?. (3rd July 2017) - Arif, Ahmed A.; Racine, Elizabeth F.
ABSTRACT: Objective : The objective of this study was to examine the relationship of breastfeeding duration with childhood asthma among low-income families in Karachi, Pakistan. Methods : Mothers/caregivers of 200 children with asthma and an equal number of children without asthma were interviewed about breastfeeding duration. Based on the responses, 6 different binary variables were constructed: breastfeeding 3 months or less, 6 months or less, 9 months or less, 12 months or less, 18 months or less, and 24 months or less. Asthma status of the child was determined by clinical examination by a primary care physician. Data was analyzed using multiple logistic regression method, adjusted for age and sex of the child, household income, parental ethnicity, number of older siblings, family history of asthma or hay fever, presence of mold, parental smoking, number of people in the household, and body mass index of the child. Results : The average duration of breastfeeding was 21.4 months ( SD = 7.33 months). Breastfeeding for at least 24 months was associated with increased odds of asthma (aOR = 1.77, 95%CI: 0.99, 3.16). Whereas breastfeeding for 12 months or less, and to some extent 18 months or less, was protective against childhood asthma. There was some evidence this protective effect may be delayed in children with a family history of asthma or hay fever. Conclusions : This study found breastfeeding for 12 months or less may have a protective effect against asthma. The protective effect weans down after 18 months, and if continued 24 months or more may place the child at-risk of asthma.